Analysis of efforts to encourage employee performance improvement - Putra, Rio; Syafwandi, Syafwandi; Lusiana, Lusiana (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
The purpose of this study is to find out how communication, work ethic, and the environment as well as the perception of organizational support affect teacher performance. Employee performance is one of the key factors that determine the success and competitiveness of an organization, including in the banking industry. In the banking sector, employee performance not only has an impact on operational efficiency, but also has a direct impact on the quality of service to customers, customer satisfaction, and the bank's reputation. Design/methodology/approach: A structural equation model, also known as a structural equation (SEM), is used in this work to resize the sample. This shows that SEM research using the MLE estimation model should use a minimum of 200 samples. Findings: The findings of this study show that communication and work environment can affect the improvement of employee performance, but in contrast to the work ethic in this study, it is not able to affect employee performance but is different from the case and place of the study. Research, Practical & Social Implications: The study concludes that to maintain employee performance, companies can update the work environment so that it becomes comfortable in the workplace and can improve communication both from leaders to employees and vice versa. The conclusion of this study is expected to advance management science, especially human resources.